Publication behavior in different fields of business administration: From anecdotal to empirical evidence - Mario Fernandes; Andreas Walter (Schmalenbach Journal of Business Research (SBUR), 2022)
In this paper, we substitute anecdotal with empirical evidence regarding the publication behavior of German business administration professors. We find that in particular the publication behavior of accounting researchers differs strongly from the publication behavior of researchers in other business administration fields with respect to (i)~the national focus, (ii) the focus on practitioner journals, (iii) the focus on particularly renowned journals, and (iv) the holistic publication output. More precisely, we document that accounting professors have a~stronger national focus, publish more in practitioner journals, and publish less in particularly renowned journals. Overall, our analyses document distinct differences in publication behavior across the fields of business administration, which should presumably being considered when evaluating the publication portfolios of professors across fields, e.g., in the context of resource allocation in business administration faculties.
Keywords: 650; Business administration; Journal rankings; Journal ratings; Publication behavior; Research evaluation